PENGETAHUAN DAN SIKAP GURU SEKOLAH DASAR TENTANG KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN JASMANI PADA KECAMATAN MANGGALA MAKASSAR - Abdul Rahman; Agus Sutriawan; Fahrizal Fahrizal; Andi Nurzakiah Amin (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2022)
The purpose of this study was to determine the knowledge of elementary school teachers about the 2013 curriculum, related to curriculum concepts, analysis of teaching materials, and the design of learning models, to determine the attitudes of elementary school teachers about the curriculum, related to basic concepts, analysis of teaching materials, and design of learning models. This research is a descriptive study using a quantitative approach through questionnaires, documentation, and interviews. Furthermore, data management was carried out using percentage statistical analysis with the help of the Microsoft office excel 2007 program. The results of the research on teacher knowledge of 31 teachers who were tested about the 2013 curriculum concept with a percentage of 80.65% or an average of 25 teachers were in the Less category, regarding Material Analysis Teaching with a percentage of 67.74% or an average of 21 teachers is in the Less category, regarding designing learning models with a percentage of 74.19% or an average of 23 teachers is in the Less category. Overall, the results of the study of elementary school teachers' knowledge of the 2013 Curriculum of Physical Education subjects in Manggala District or an average of 22 teachers with a percentage of 70.90% are at the Less category level. The results of the research on teacher attitudes from 31 teachers who were tested about the concept of the 2013 curriculum, a percentage of 79.35% and are in the Agree category, regarding the Analysis of Teaching Materials are stated to Agree with a percentage of 80.81% and are in the Strongly Agree category, regarding the design of learning models stated with a percentage of 79.92% in the Agree category. Overall, the results of the study of the Attitudes of Elementary School Teachers regarding the 2013 Curriculum for Physical Education subjects in Manggala District with a percentage of 80.09% are at the Strongly Agree category level.